Development of a Programming Course for Students of a Teacher Training Higher Education Institution Using the Programming Language Python - Semenovich Prokopyev, Mikhail (2020)
At present, teaching programming to future teachers is superficial or is excluded from computer science curricular. Only programming fundamentals are taught during computer studies, and skills acquired during the training are not applied in practice. The aims of this article are 1) to develop a programming course for teacher training disciplines that are taught in training units of the Ammosov North-Eastern Federal University (NEFU), and 2) give recommendations to apply features of the programming language Python in the professional activities of future teachers. This work applies the iterative methodological approach to undertake the study in various groups of students of NEFU from 2016 to 2019. Quantitative and objective indicators are used. Results show which modules of Python are the most appropriate for students to study for their future professional teaching activities. The training course "Use of the language Python by future teachers" is developed, and will be taught in all training units of the university, that have teacher training disciplines. The article determines a direction of future research related to teaching programming, which is important for all computer studies.